VDC_100102371237.0X000001. Issue 10 (October 2018) - Teeter, William A.; Bradley, Matthew J.; Romagnoli, Anna; Hu, Peter; Li, Yao; Stein, Deborah M.; Scalea, Thomas M.; Brenner, Megan
The purpose of this study is to compare end-tidal carbon dioxide (EtCO2 ) during resuscitation of open-chest cardiac massage (OCCM) with aortic cross-clamp (ACC) versus receiving resuscitative endovascular balloon occlusion of the aorta (REBOA) with closed-chest compressions (CCCs). Patients who received REBOA were compared with patients receiving OCCM for traumatic arrest using continuous vital sign monitoring and videography. Thirty-three patients were enrolled in the REBOA group and 18 patients were enrolled in the OCCM group. Of the total patients, 86.3 per cent were male with a mean age of 36.2 ± 13.9 years. Ninety-four percent of patients suffered penetrating trauma in the OCCM group compared with 30.3 per cent of the REBOA group ( P = <0.001). Before aortic occlusion (AO), there was no difference in initial EtCO2 values, but mean, median, peak, and final EtCO2 values were lower in OCCM ( P < 0.005). During CPR after AO, the initial, mean, and median values were higher with REBOA ( P = 0.015, 0.036, and 0.038). The rate of return of spontaneous circulation was higher in REBOA versus OCCM (20/33 [60.1%] vs 5/18 [33.3%]; P = 0.04), and REBOA patients survived to operative intervention more frequently ( P = 0.038). REBOA patients had greater total cardiac compression fraction (CCF) before AO than OCCM (85.3 ± 12.7% vs 35.2 ± 18.6%, P < 0.0001) and after AO (88.3 ± 7.8% vs 71.9 ± 24.4%, P = 0.0052). REBOA patients have higher EtCO2 and cardiac compression fraction before and after AO compared with patients who receive OCCM.